Estudo de superfícies inteligentes para desenvolvimento de nanobiossensores - Silva, Aline Cristine Nanuh da (2014)
The use of herbicides has increased considerably in recent years and as a consequence, it has also been an increased exposure of ecosystems and human life to these highly toxic compounds. The study and development of metolodologies with greater sensitivity, which aims at the detection of these pesticides, are becoming extremely relevant. Thus, this study aimed to study the development of a nanobiosensor applying functionalized AFM tips and Atomic Force Spectroscopy (AFS) for detection of herbicides imazaquin and metsulfuronmethyl, ALS inhibitors. We studied the force and work of adhesion between AFM tips, unmodified and chemically modified by immobilization of ALS, and substrates contaminated with imazaquin and metsulfuron-methyl. In addition, the tips were characterized by infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). It was possible to see differences between the tips functionalized and not functionalized, analyze the properties of each individual and develop a nanobiosensor for detection of herbicides.